Coppers from the Battle of Trafalgar: metallurgical analysis of structural fastenings from the French ships Fougueux (1785-1805) and Bucentaure (1804-1805) - de Rosa, Horacio Manuel (2015)
In this paper, the characterization results of an array of copper spikes, recovered from the Camposoto site (San Fernando,Andalusia, Spain), are presented. The research of the site, developed by the Underwater Archaeology Centre (CAS) of theAndalusian Historical Heritage Institute (IAPH), allowed identifying the underwater remains as the French Navy ship Fougueux(1785-1805). This was a 74-gun ship, one of the vessels of the combined Franco-Spanish fleet, which on October 21st, 1805,fought against a British fleet in the Battle of Trafalgar. By means of Optical Microscopy (OM) and Scanning ElectronMicroscopy (SEM), information about the thermo-mechanical processes which affected the objects was obtained. In addition, thechemical composition of the materials was determined by Energy Dispersive X-ray Spectrometry (EDXRS). This data isconsidered a good indicative of the last steps of the manufacturing process and the quality of the alloys used. Aiming to performa comparative study, some samples from the site Bajo Chapitel (located in the Cadiz Bay), were analyzed. The artifacts of thissite are most likely associated with the Bucentaure (1804-1805), another French ship that fought in the mentioned battle.